2015
DOI: 10.18410/jebmh/2015/946
|View full text |Cite
|
Sign up to set email alerts
|

A Study of Impaired Glucose Tolerance Test in Pulmonary Tuberculosis

Abstract: The link between Diabetes mellitus & Tuberculosis has been recognizing for centuries. Recently Tuberculosis has re-emerged as a major health concern. There is growing evidence that Diabetes mellitus with Tuberculosis may affect disease presentation and treatment. The Tuberculosis also influences glucose intolerance and influences the glycaemic control in the people with Diabetes mellitus. Approximately 2 Million persons worldwide died of Tuberculosis and 9 Million become infected each year. (CDC, 2007) 1. With… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…TB patients with T2DM were found predisposed to infection relapses, treatment failures, increased mortality, delayed mycobacterial clearance as observed by previous studies [ 7 - 9 ]. The IGT may occur transiently during pulmonary TB owing to the stress of prevailing infection and it has been shown to improve following effective anti-tubercular therapy [ 10 ]. Previous studies have shown a high prevalence of abnormal glucose tolerance (GT) in TB patients with rates ranging from 2% to 41% after OGTT [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…TB patients with T2DM were found predisposed to infection relapses, treatment failures, increased mortality, delayed mycobacterial clearance as observed by previous studies [ 7 - 9 ]. The IGT may occur transiently during pulmonary TB owing to the stress of prevailing infection and it has been shown to improve following effective anti-tubercular therapy [ 10 ]. Previous studies have shown a high prevalence of abnormal glucose tolerance (GT) in TB patients with rates ranging from 2% to 41% after OGTT [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…The avoidable loss is more due to insect pests. Lakra and Bhatti (1985) reported that as many as 130 species of insect pests on ber in India, but only few species have attained the status of the pest and cause considerable damage. Jothi and Tandon (1995); Patil and Patil (1996); Kavitha et al, (2002); Balikai (1999); Haldhar et al, 2016 andKaruppaiah et al, 2010 recorded seveal insect-pests and non insect pests on ber in Karnataka, Andra Pradesh and Rajasthan Apart from several important insect pests causing damage to ber, one such insect pest that feeds on ber leaf is Tarucus indica Evans (Lycaenidae: Lepidoptera).…”
Section: Examples Of Ant-lepidoptera Interactionsmentioning
confidence: 99%
“…The avoidable loss is more due to insect pests. Lakra and Bhatti (1985) reported that as many as 130 species of insect pests on ber in India, but only few species have attained the status of the pest and cause considerable damage. Jothi and Tandon (1995); Patil and Patil (1996); Kavitha et al, (2002); Balikai (1999); Haldhar et al, 2016 andKaruppaiah et al, 2010 recorded seveal insect-pests and non insect pests on ber in Karnataka, Andra Pradesh and Rajasthan Apart from several important insect pests causing damage to ber, one such insect pest that feeds on ber leaf is Tarucus indica Evans (Lycaenidae: Lepidoptera).…”
Section: Examples Of Ant-lepidoptera Interactionsmentioning
confidence: 99%